African Fertilizer and Soil Health Action Plan - Mutamba, Manyewu (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This presentation was made at the Africa Fertilizer and Soil Health Summit 2024 on the African Fertilizer and Soil Health Action Plan (2024-2034)